Implementasi Pemetaan Perilaku Hidup Bersih Sehat Menggunakan Framework CodeIgniter dan Google Maps API (Studi Kasus Dinas Kesehatan Kota Salatiga) - Ade Kresna Dewantara; Evangs Mailoa (AITI, 2019)
Health Department of Salatiga is one of public Health Department which is give service and information about health in Salatiga. One that is less published information from Health Department of Salatiga is healthy hygienic behavior. This information important to be known by the public so that public can active in overcome about health issues. Absence of media and methods of data collection which is not relevant make this information not published by Health Department of Salatiga. This research apply the codeigniter technology and google maps api to build the geographic information system. The purpose of using this technology because codeigniter technology has been provide lots of divining manual to accelerate making an application. The technology API and Google Maps can be used to mapping PHBS level in small region at Salatiga city. Mapping result can used by public to obtain information about PHBS level in Salatiga city, so it can be used as reference for improving PHBS level by increasing health hygienic behavior.